Crop Composition and Density after Tbinnings and before Final Felling in the Matang Mangrove Reserve, Perak - Soon Poh, Tay; Srivastava, P.B.L (1982)
The study reports the composition of the crop and growth pattern of important species in terms of height, density, diameter and basal area during the rotation period in some productive stands of the Matang Mangrove Reserve of Peninsular Malaysia. In all, seven stands representing areas before thinning J, thinning II, thinning III and before final felling were sampled. A II the sites were potential Rhizophora spp. stands belonging to Watson's inundation classes II and III. The crop was almost pure and uniform, dominated by Rhizophora apiculata. Brugiera parviflora, the most important associate was found to constitute less than 10 per cent of the crop in most of the sampled plots. On an average, there were 3236, 2107, 1321 and 830 stems per hectare before thinning I, II, III and final felling respectively. Mean DBH for the respective stages were 8.28 em, 9.65 em, 13.90 em and 17.45 em. When compared with earlier estimates, it appears that there is a large scale mortality between 2 and 15 years of crop. There is a need to study the mortality rate and its causes during this period which might have a bearing on the thinning schedules and rotation period.